Analisis Kemampuan Pemahaman Konsep Matematis Siswa pada Pembelajaran Matematika Kelas XI IIS SMA PGRI 3 Padang - Ibnu S Ibnu S; Radhya Yusri; Lucky Heriyanti Jufri (Horizon, 2021)
This research is motivated by the low ability of students to understand mathematical concepts in learning mathematics.The purpose of this study was to determine how thw mathematical ability of class XI IIS students at SMA PGRI 3 Padang. The subjects of this study were students of class XI IIS SMA PGRI 3 Padang, totalling 19 students. The research method used is descriptive method using a qualitative approach. The instrument used in this study was a test of the ability to understand concepts in the form of 4 questions in the form of descriptions and interview. The test results were analysed based on indicators of concept understanding. The results of this study indicate hat the results of data analysis on the ability to understand mathematical concepts of the 19 students tested obtained the total qualification score of 50% in the medium category. The qualifications for the total score of students mathematical concept understanding abilities based on the analysis of eachindicator on concept undestandig are as follow: on the indicator of restating a concept, 54% is in the medium category, classifying objects according to certain properties (according to the concept) is 82% are in the high category, providing examples and non-examples of the concept are 30 in the less category, presenting the concept in the form of a mathematical representation is 35% in the less category, developing necessary or sufficient requirements of a conceptis 73% in the medium category, and applying the concept or problem-solving algorithm is 24% in the lo category.